PDGF Receptor Alpha Signaling Is Key for Müller Cell Homeostasis Functions - Díaz-Lezama, Nundehui (Int J Mol Sci, 2021)
Müller cells, the major retinal macroglia, are key to maintaining vascular integrity as well as retinal fluid and ion homeostasis. Although platelet derived growth factor (PDGF) receptor expression in Müller glia has been reported earlier, their actual role for Müller cell function and intimate interaction with cells of the retinal neurovascular unit remains unclear. To close this gap of knowledge, Müller cell-specific PDGF receptor alpha (PDGFRα) knockout (KO) mice were generated, characterized, and subjected to a model of choroidal neovascularization (CNV). PDGFRα-deficient Müller cells could not counterbalance hypoosmotic stress as efficiently as their wildtype counterparts. In wildtypes, the PDGFRα ligand PDGF-BB prevented Müller cell swelling induced by the administration of barium ions. This effect could be blocked by the PDGFR family inhibitor AC710. PDGF-BB could not restore the capability of an efficient volume regulation in PDGFRα KO Müller cells. Additionally, PDGFRα KO mice displayed reduced rod and cone-driven light responses. Altogether, these findings suggest that Müller glial PDGFRα is central for retinal functions under physiological conditions. In contrast, Müller cell-specific PDGFRα KO resulted in less vascular leakage and smaller lesion areas in the CNV model. Of note, the effect size was comparable to pharmacological blockade of PDGF signaling alone or in combination with anti-vascular endothelial growth factor (VEGF) therapy—a treatment regimen currently being tested in clinical trials. These data imply that targeting PDGF to treat retinal neovascular diseases may have short-term beneficial effects, but may elicit unwarranted side effects given the putative negative effects on Müller cell homeostatic functions potentially interfering with a long-term positive outcome.